Towards high‐resolution synchrotron radiation imaging with statistical iterative reconstruction. (26th December 2012) - Rashed, Essam A.; Kudo, Hiroyuki
Abstract : Synchrotron radiation (SR) X‐ray micro‐computed tomography (CT) is an effective imaging modality for high‐resolution investigation of small objects, with several applications in medicine, biology and industry. However, the limited size of the detector field of view (FOV) restricts the sample dimensions to only a few millimeters. When the sample size is larger than the FOV, images reconstructed using conventional methods suffer from DC‐shift and low‐frequency artifacts. This classical problem is known as the local tomography or the interior problem. In this paper, a statistical iterative reconstruction method is introduced to eliminate image artifacts resulting from the local tomography. The proposed method, which can be used in several SR imaging applications, enables high‐resolution SR imaging with superior image quality compared with conventional methods. Real data obtained from different SR micro‐CT applications are used to evaluate the proposed method. Results indicate a noteworthy quality improvement in the image reconstructed from the local tomography measurements.